Promoting effect of MXenes on 1T/2H–MoSe2 for hydrogen evolution. Issue 27 (24th June 2021) - Shao, Zhitao; Wu, Lili; Ye, Hongfeng; Ma, Xinzhi; Zhang, Xitian; Li, Lu
Abstract : The 1T/2H–MoSe2 /Ti3 C2 composites integrated via a facile hydrothermal method exhibit an optimal overpotential of 150 mV at 10 mA cm −2 in 1 M KOH, indicating that Ti3 C2 is an ideal conductive support for building highly efficient electrocatalysts. Abstract : Cost-effective electrocatalysts are imperative to the large-scale hydrogen evolution reaction. Herein, 1T/2H–MoSe2 /Ti3 C2 composites are integrated via a hydrothermal method by taking advantage of the tunable phases of MoSe2 and high conductivity of Ti3 C2 . Consequently, the 1T/2H–MoSe2 /Ti3 C2 composites exhibit an optimal overpotential of 150 mV at 10 mA cm −2, a low Tafel slope of 90 mV dec −1, and a steady catalytic activity for over 30 h in an alkaline environment. The improved HER performances can be ascribed to the introduction of the Ti3 C2 support in a proper proportion, which not only makes the charge transfer process more convenient but also helps the dispersion of MoSe2 . Furthermore, the formation of MoSe2 /Ti3 C2 heterogeneous interfaces and the synergistic effects stemming from the intimate interactions between the individual components ultimately boost the H2 O dissociation in the Volmer step. This study indicates that Ti3 C2 is an ideal conductive support for improving HER catalytic activity, and paves a new way for other transition metal selenides and MXenes to build highly efficient HER electrocatalysts.